Approach to the Diagnosis and Management of Ptosis - Wahju Ratna Martiningsih; Andra Novitasari; Yusri Candra Alim; Aliyah Ari Juliani; Farras Syahla Salsabilla (Nusantara Science and Technology Proceedings, 2024)
Ptosis is a condition characterized by the drooping of the upper eyelid from its normal position. This case report presents a 45-year-old female patient who has experienced the inability to fully open her right upper eyelid for the past 2 months, a condition that appeared suddenly. This persistent issue has significantly impacted her daily activities. The patient has a history of a fall 8 years ago, resulting in a laceration on her right forehead that required suturing. Ophthalmologic evaluation revealed a visual acuity of 20/30 in the right eye and 20/25 in the left eye. Physical examination confirmed ptosis of the right upper eyelid (oculi dextra). Other anterior segment findings were within normal limits. Extraocular movements were intact in all directions with normal direct and consensual pupillary reflexes. Specific measurements for the right eye included a palpebral fissure height of 6 mm, Margin Reflex Distance 1 (MRD1) of 0 mm, and Margin Reflex Distance 2 (MRD2) of 6 mm, with a levator function of 8 mm. Based on the history, physical examination, ophthalmologic findings, and ancillary tests, the patient was diagnosed with ptosis oculi dextra. The treatment plan included administration of vitamin B complex and vitamin B12, along with a referral to an ophthalmologist for surgical management of ptosis.